Cerebral Intraventricular Hemorrhage and Interleukin-6 in Preterm Neonates - Mahnaz Fouladinejad; Hadi Khorsand Zak; Shahin SHirvani; Mahsa Besharat; Ehsan Alaee (Mashhad University of Medical Sciences, 2020)
Background: Intraventricular hemorrhage (IVH) in preterm neonates is a serious problem in neonatal intensive care units (NICU) worldwide. IVH is reported in approximately 60-70% of very-low-birth-weight (VLBW) neonates. The present study aimed to assess the association of IVH with neonatal characteristics and serum markers, such as serum Interleukin-6 (IL-6) level, in preterm neonates in an academic hospital in the Northeast of Iran. Methods: In this cross-sectional study, a number of 71 VLBW preterm neonates (≤34 weeks of gestational age (GA), birth weight (BW) ≤1500g) were examined regarding the evidence of IVH up to the 40th week of GA in Gorgan, Northeast of Iran. The serum interleukin-6 (IL-6) level was measured within the first 12 hours of lifebirth. The association among the variables was analyzed in SPSS software (version 16) using the chi-square test. Results: Out of 56 preterm neonates who survived until the 40th week, 15 (26.8%) cases demonstrated evidence of IVH at discharge, they had a significantly lower GA (29.04±2 weeks vs. 30.44±1.7 weeks; P=0.003) and BW (1075.43±208 kg vs. 1251.6±199.4 kg; P=0.001), as compared to 41(73.2%) newborns with no IVH. Preterm neonates with IVH had a significantly higher IL-6 serum level, as compared to those without IVH (224±210 pg/ml vs. 91.93±138 pg/ml; P=0.035). Conclusion: As evidenced by the obtained result, low birth weight and premature birth could be serious risk factors for the development of IVH. Furthermore, IL-6 concentration may play a pivotal role in the occurrence of IVH.